Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's analyze each of the given compound inequalities step-by-step to find out which one has no solution.
1. [tex]\(3(x+1) \geq 2(x+5)\)[/tex] and [tex]\(-2(x+1) \leq 3(x+1)\)[/tex]
First inequality:
[tex]\[ 3(x + 1) \geq 2(x + 5) \][/tex]
[tex]\[ 3x + 3 \geq 2x + 10 \][/tex]
[tex]\[ 3x - 2x \geq 10 - 3 \][/tex]
[tex]\[ x \geq 7 \][/tex]
Second inequality:
[tex]\[ -2(x + 1) \leq 3(x + 1) \][/tex]
[tex]\[ -2x - 2 \leq 3x + 3 \][/tex]
[tex]\[ -2 - 3 \leq 3x + 2x \][/tex]
[tex]\[ -5 \leq 5x \][/tex]
[tex]\[ -1 \leq x \][/tex]
Combining the two:
[tex]\[ -1 \leq x \quad \text{and} \quad x \geq 7 \][/tex]
This simplifies to:
[tex]\[ x \geq 7 \][/tex]
So, this set of inequalities has a solution where [tex]\( x \geq 7 \)[/tex].
2. [tex]\(2x - 1 < x - 4\)[/tex] and [tex]\(-4x + 3 > 2x - 9\)[/tex]
First inequality:
[tex]\[ 2x - 1 < x - 4 \][/tex]
[tex]\[ 2x - x < -4 + 1 \][/tex]
[tex]\[ x < -3 \][/tex]
Second inequality:
[tex]\[ -4x + 3 > 2x - 9 \][/tex]
[tex]\[ -4x - 2x > -9 - 3 \][/tex]
[tex]\[ -6x > -12 \][/tex]
[tex]\[ x < 2 \][/tex]
Combining the two:
[tex]\[ x < -3 \quad \text{and} \quad x < 2 \][/tex]
This simplifies to:
[tex]\[ x < -3 \][/tex]
So, this set of inequalities has a solution where [tex]\( x < -3 \)[/tex].
3. [tex]\(-3x - 1 \leq 2x + 9\)[/tex] and [tex]\(-4x + 3 > -2x + 11\)[/tex]
First inequality:
[tex]\[ -3x - 1 \leq 2x + 9 \][/tex]
[tex]\[ -3x - 2x \leq 9 + 1 \][/tex]
[tex]\[ -5x \leq 10 \][/tex]
[tex]\[ x \geq -2 \][/tex]
Second inequality:
[tex]\[ -4x + 3 > -2x + 11 \][/tex]
[tex]\[ -4x + 2x > 11 - 3 \][/tex]
[tex]\[ -2x > 8 \][/tex]
[tex]\[ x < -4 \][/tex]
Combining the two:
[tex]\[ x \geq -2 \quad \text{and} \quad x < -4 \][/tex]
There is no [tex]\( x \)[/tex] that satisfies both conditions simultaneously. Therefore, this set of inequalities has no solution.
4. [tex]\(2x - 5 \leq 3x + 5\)[/tex] and [tex]\(-4x - 1 > 2x + 3\)[/tex]
First inequality:
[tex]\[ 2x - 5 \leq 3x + 5 \][/tex]
[tex]\[ 2x - 3x \leq 5 + 5 \][/tex]
[tex]\[ -x \leq 10 \][/tex]
[tex]\[ x \geq -10 \][/tex]
Second inequality:
[tex]\[ -4x - 1 > 2x + 3 \][/tex]
[tex]\[ -4x - 2x > 3 + 1 \][/tex]
[tex]\[ -6x > 4 \][/tex]
[tex]\[ x < -\frac{2}{3} \][/tex]
Combining the two:
[tex]\[ x \geq -10 \quad \text{and} \quad x < -\frac{2}{3} \][/tex]
This simplifies to:
[tex]\[ -10 \leq x < -\frac{2}{3} \][/tex]
So, this set of inequalities has a solution in the range [tex]\([-10, -\frac{2}{3}]\)[/tex].
After analyzing all the inequalities, we find that the compound inequality:
[tex]\[ -3x - 1 \leq 2x + 9 \quad \text{and} \quad -4x + 3 > -2x + 11 \][/tex]
has no solution.
Therefore, the answer is [tex]\( \boxed{3} \)[/tex].
1. [tex]\(3(x+1) \geq 2(x+5)\)[/tex] and [tex]\(-2(x+1) \leq 3(x+1)\)[/tex]
First inequality:
[tex]\[ 3(x + 1) \geq 2(x + 5) \][/tex]
[tex]\[ 3x + 3 \geq 2x + 10 \][/tex]
[tex]\[ 3x - 2x \geq 10 - 3 \][/tex]
[tex]\[ x \geq 7 \][/tex]
Second inequality:
[tex]\[ -2(x + 1) \leq 3(x + 1) \][/tex]
[tex]\[ -2x - 2 \leq 3x + 3 \][/tex]
[tex]\[ -2 - 3 \leq 3x + 2x \][/tex]
[tex]\[ -5 \leq 5x \][/tex]
[tex]\[ -1 \leq x \][/tex]
Combining the two:
[tex]\[ -1 \leq x \quad \text{and} \quad x \geq 7 \][/tex]
This simplifies to:
[tex]\[ x \geq 7 \][/tex]
So, this set of inequalities has a solution where [tex]\( x \geq 7 \)[/tex].
2. [tex]\(2x - 1 < x - 4\)[/tex] and [tex]\(-4x + 3 > 2x - 9\)[/tex]
First inequality:
[tex]\[ 2x - 1 < x - 4 \][/tex]
[tex]\[ 2x - x < -4 + 1 \][/tex]
[tex]\[ x < -3 \][/tex]
Second inequality:
[tex]\[ -4x + 3 > 2x - 9 \][/tex]
[tex]\[ -4x - 2x > -9 - 3 \][/tex]
[tex]\[ -6x > -12 \][/tex]
[tex]\[ x < 2 \][/tex]
Combining the two:
[tex]\[ x < -3 \quad \text{and} \quad x < 2 \][/tex]
This simplifies to:
[tex]\[ x < -3 \][/tex]
So, this set of inequalities has a solution where [tex]\( x < -3 \)[/tex].
3. [tex]\(-3x - 1 \leq 2x + 9\)[/tex] and [tex]\(-4x + 3 > -2x + 11\)[/tex]
First inequality:
[tex]\[ -3x - 1 \leq 2x + 9 \][/tex]
[tex]\[ -3x - 2x \leq 9 + 1 \][/tex]
[tex]\[ -5x \leq 10 \][/tex]
[tex]\[ x \geq -2 \][/tex]
Second inequality:
[tex]\[ -4x + 3 > -2x + 11 \][/tex]
[tex]\[ -4x + 2x > 11 - 3 \][/tex]
[tex]\[ -2x > 8 \][/tex]
[tex]\[ x < -4 \][/tex]
Combining the two:
[tex]\[ x \geq -2 \quad \text{and} \quad x < -4 \][/tex]
There is no [tex]\( x \)[/tex] that satisfies both conditions simultaneously. Therefore, this set of inequalities has no solution.
4. [tex]\(2x - 5 \leq 3x + 5\)[/tex] and [tex]\(-4x - 1 > 2x + 3\)[/tex]
First inequality:
[tex]\[ 2x - 5 \leq 3x + 5 \][/tex]
[tex]\[ 2x - 3x \leq 5 + 5 \][/tex]
[tex]\[ -x \leq 10 \][/tex]
[tex]\[ x \geq -10 \][/tex]
Second inequality:
[tex]\[ -4x - 1 > 2x + 3 \][/tex]
[tex]\[ -4x - 2x > 3 + 1 \][/tex]
[tex]\[ -6x > 4 \][/tex]
[tex]\[ x < -\frac{2}{3} \][/tex]
Combining the two:
[tex]\[ x \geq -10 \quad \text{and} \quad x < -\frac{2}{3} \][/tex]
This simplifies to:
[tex]\[ -10 \leq x < -\frac{2}{3} \][/tex]
So, this set of inequalities has a solution in the range [tex]\([-10, -\frac{2}{3}]\)[/tex].
After analyzing all the inequalities, we find that the compound inequality:
[tex]\[ -3x - 1 \leq 2x + 9 \quad \text{and} \quad -4x + 3 > -2x + 11 \][/tex]
has no solution.
Therefore, the answer is [tex]\( \boxed{3} \)[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.